The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3389/fmed.2022.924267
|View full text |Cite
|
Sign up to set email alerts
|

Individuals With Higher CD4/CD8 Ratio Exhibit Increased Risk of Acute Respiratory Distress Syndrome and In-Hospital Mortality During Acute SARS-CoV-2 Infection

Abstract: BackgroundCD4/CD8 ratio has been used as a quantitative prognostic risk factor in patients with viral infections. This study aims to assess the association between in-hospital mortality and at admission CD4/CD8 ratio among individuals with acute SARS-CoV-2 infection.MethodsThis is a longitudinal cohort study with data of all consecutive patients admitted to the COVID-19 unit at Hospital del Mar, Barcelona, Spain for ≥48 h between March to May 2020. The CD4+ CD8+ T-cell subset differentiation was assessed by fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 31 publications
(39 reference statements)
1
8
0
Order By: Relevance
“…The FACS results showed that both MIF knockout and infection time affected the CD3 + CD8 − / CD3 + CD8 + ratio. Additionally, the ratio increased in both the WTs7 and KTs7 groups, which is similar to the results of a previous study, reflecting changes in the host immune response 75,76 . Increased IL‐4 and decreased IFN‐γ levels could be observed in the spleen of the WT and MIF KO mice at 14 and 35 dpi, except for the increase in IFN‐γ at 7 dpi.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The FACS results showed that both MIF knockout and infection time affected the CD3 + CD8 − / CD3 + CD8 + ratio. Additionally, the ratio increased in both the WTs7 and KTs7 groups, which is similar to the results of a previous study, reflecting changes in the host immune response 75,76 . Increased IL‐4 and decreased IFN‐γ levels could be observed in the spleen of the WT and MIF KO mice at 14 and 35 dpi, except for the increase in IFN‐γ at 7 dpi.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, the ratio increased in both the WTs7 and KTs7 groups, which is similar to the results of a previous study, reflecting changes in the host immune response. 75,76 Increased IL-4 and decreased IFN-γ levels could be observed in the spleen of the WT and MIF KO mice at 14 and 35 dpi, except for the increase in IFN-γ at 7 dpi. Anti-inflammatory IL-4 could enhance the intestinal epithelium barrier, while proinflammatory IFN-γ could injure the gut barrier.…”
Section: Discussionmentioning
confidence: 95%
“…The most vulnerable groups of patients with the highest risk of a severe infection include elderly persons and immunocompromised people. People living with HIV are a non-homogeneous group of immunocompromised persons, which includes both low CD4 count and ongoing immune activation impacting the response differently to and course of other viral infections [ 3 , 4 ]. Detectable viral load and concomitant chronic comorbidities independently increase the risk of severe outcomes of COVID-19 in this group of patients [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…have been associated with increased risk of fatal outcomes during acute Covid-19 [24]. However, the CD4 + /CD8 + T-cell ratio appears to remain constant during SARS-CoV-2 infection in PWH compared with HIV-uninfected individuals in whom the ratio is increased [25].…”
Section: T-cell Cross-reactivity To Omicronmentioning
confidence: 98%
“…A total of 24 HIV-uninfected women (n = 12 pregnant, n = 12 postpartum) and 15 WLWH (n = 5 pregnant n = 5 postpartum, n = 5 not pregnant) were recruited with a median age of 30 years (IQR: [22][23][24][25][26][27][28][29][30][31][32][33] and 34 years (IQR: 29-40; p = 0.035), respectively. Most of the participants (56.4%, 22/39) had been infected with the Beta variant (B.…”
Section: Characteristics Of Enrolled Participantsmentioning
confidence: 99%